L’estil nominalitzat - Salvador, Vicent (Caplletra. Revista Internacional de Filologia, 2000)
This paper deals with the subject of nominal(ized) style in contrast with clausal style. Expressing processes and qualities as entities involves a certain kind of metaphor –a grammatical metaphor, in the sense systemic functional linguistic conceives it. Furthermore this device is useful to improve the development of the thematic progression of a text. Nominalized style is characteristic of scientific academic discourse, but it widely spreads along other types of discourse, implying sometimes an effect of abstraction and opacity unsuitable for other discursive purposes and specially for literary genres.